Imported Dengue Fever in Milan, Italy: A Seven-Year Retrospective Study - Pieruzzi, Margherita Eleonora; Mileto, Davide; Behring, Alessandra Helen; Caronni, Stefania; Mancon, Alessandro; Vezzosi, Luigi; Rizzo, Alberto; Poloni, Andrea; Gori, Andrea; Giacomelli, Andrea; Antinori, Spinello (Infectious disease reports, 2025)
Background: Dengue fever is an arboviral infection transmitted by Aedes mosquitoes that has recently become a public health concern also in Europe, causing many outbreaks of autochthonous cases. Methods: We retrospectively retrieved dengue cases in returning travelers from tropical areas diagnosed at the Luigi Sacco Hospital between January 2018 and December 2024. All patients with positive serology for DENV (IgM alone or IgM and IgG or neutralizing antibodies detection) and/or positive real-time polymerase chain reaction (RT-PCR) for DENV RNA on plasma and urine were considered. Analyses were descriptive. Results: This analysis included 159 travelers with confirmed (n = 138; 86.8%) or probable (n = 21; 13.2%) dengue fever. The median age was 38 years (interquartile range [IQR] 30–50); 87 (54.7%) were females. The median time between symptom onset and seeking medical attention was four days (IQR 3–6); 29.6% required hospitalization, with a median stay of four days (IQR 0–5). The most common symptoms included fever (100%), myalgia (52.2%), and headache (49.1%). Laboratory findings revealed thrombocytopenia (53.8%), leukopenia (64.1%), elevated ALT (51.9%), and LDH (60.2%). Among the confirmed cases, 128 (92.8%) were diagnosed with RT-PCR. Serotypes 1 and 2 were the most prevalent (28.9% and 27.3%, respectively). Most cases were classified as dengue without warning signs (150, 94.3%), eight cases (5.0%) as dengue with warning signs, and one as severe dengue. Conclusions: Dengue fever is an important cause of fever among travelers returning to Italy from endemic areas. Although severe dengue is rare among travelers, further prospective studies need to address this issue. Diagnosis should be pursued by using molecular tools because of cross-reactivity with other arboviruses.